Exploiting amphiphilicity: facile metal free access to thianthrenes and related sulphur heterocycles1. Issue 44 (4th June 2015) - Pawliczek, Martin; Garve, Lennart K. B.; Werz, Daniel B.
<x xml:space="preserve">Abstract</x> Benzodithioloimine containing a positively and a negatively polarised sulphur is an ideal precursor for thianthrenes and related heterocycles.